Ionospheric Non-linear Effects Observed During Very-Long-Distance HF Propagation - Yampolski, Yuri; Milikh, Gennady; Zalizovski, Andriy; Koloskov, Alexander; Reznichenko, Artem; Nossa, Eliana; Bernhardt, Paul A.; Briczinski, Stan; Grach, Savely M.; Shindin, Alexey; Sergeev, Evgeny (Frontiers in Astronomy and Space Sciences, 2019)
A new super-long-range wave propagation technique was implemented at different HF heating facilities. The HF waves radiated by a powerful heater were scattered into the ionospheric waveguide by the stimulated field aligned striations. This waveguide is formed in a valley region between the E- and F- layers of the ionosphere. The wave trapping and channeling provide super-long-range propagation of HF heater signals detected at the Ukrainian Antarctic “Academik Vernadsky” Station (UAS) which is many thousand kilometers away from the corresponding HF heating facility. It is objectives of this paper to study excitation of the ionospheric waveguide due to scattering of the HF heating wave by the artificial field aligned irregularities. In addition, the probing of stimulated ionospheric irregularities can be obtained from analyses of the signals received at far distance from the HF heater. The paper uses a novel method of scattering of the HF radiation by the heating facility for diagnostics of nonlinear effects at the super-long radio paths. Experiments were conducted at three different powerful HF facilities: EISCAT (Norway), HAARP (Alaska) and Arecibo (Puerto Rico) and by using different far spaced receiving sites. The key problems for super-long-range propagation regime is feeding of the ionospheric waveguide. Then the energy needs to exit from the waveguide at a specific location to be detected by the surface-based receiver. During our studies the waveguide feeding was provided by scattering of the HF waves by the artificial ionospheric turbulence (AIT) above the HF heater. An interesting opportunity for channeling of the HF signals occurs due to the aspect scattering of radio waves by field aligned irregularities (FAI), when the scattering vector is parallel to the Earth surface. Such FAIs geometry takes place over the Arecibo facility. Here FAI are oriented along the geomagnetic field line inclined by 43 degrees. Since the Arecibo HF beam is vertical, the aspect scattered waves will be oriented almost horizontally toward the South. Such geometry provides unique opportunity to channel the radio wave energy into the ionospheric waveguide and excites the whispering gallery modes.